OVERVIEW OF TEMPERATURE, PH, DO AND WATER DEPTH AT THE UNIVERSITY OF PALANGKA RAYA’S PEAT TECHNO PARK (PTP) - Erniaty; Sulmin Gumiri; Ardianor; Agus Haryono; Yulintine (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
The aquatic environment can be divided into two based on physical and chemical differences, namely: freshwater environment and marine aquatic environment. There are two kinds of freshwater waters, namely: calm (lentic) waters such as lakes, reservoirs and ponds; Flowing waters (lotic) for example rivers, sewers and ditches. In lotic habitats there are two main zones, namely the rushing water zone and the hood zone or calm zone. While in calm or lentic waters in general there are three main zones, namely: the littoral zone, the limnetic zone and the profundal zone (Cantonati et al., 2020). A water can be influenced by several factors including temperature, pH, DO and depth, therefore it is very important if in this case it is discussed about the overview of the waters at PTP Universitas Palangka Raya. By researching the parameters above, it can be seen that: Z, temperature, pH, DO. The correlation between DO and depth is -0.35** meaning it is significant at 0.01 or below 0.05. The temperature with DO is also significant but positive between temperature and DO because the value is 0.41** due to one quadrant according to PC1